2010
DOI: 10.1007/s00268-010-0407-6
|View full text |Cite
|
Sign up to set email alerts
|

Presentation and Survival of Operable Esophageal Cancer in Patients 55 Years of Age and Below

Abstract: A significant proportion (20.8%) of patients presenting with operable esophageal cancer was younger than aged 55 years. Almost two-thirds of those presenting younger than aged 55 years had T3 stage tumors, which was significantly different than those older than aged 55 years. Despite more advanced tumor stage at presentation, the prognosis of esophageal cancer for patients younger than aged 55 years is similar to those older than aged 55 years (log-rank = 0.99).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
18
0
1

Year Published

2012
2012
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(22 citation statements)
references
References 27 publications
3
18
0
1
Order By: Relevance
“…However, age was not significantly associated with outcome among the cases with oesophageal cancer in our study (Fig 1b). Similar finding was observed in a study conducted by Hamouda A et al (5) which reviewed the presentation and survival of young patients with esophageal cancer. 365 esophagectomies were performed for cancer, of which 76 patients were younger than 55 years (20.8%) and 289 were older than 55 years.…”
Section: Agesupporting
confidence: 75%
“…However, age was not significantly associated with outcome among the cases with oesophageal cancer in our study (Fig 1b). Similar finding was observed in a study conducted by Hamouda A et al (5) which reviewed the presentation and survival of young patients with esophageal cancer. 365 esophagectomies were performed for cancer, of which 76 patients were younger than 55 years (20.8%) and 289 were older than 55 years.…”
Section: Agesupporting
confidence: 75%
“…For example, in a study by Portale et al (2004), approximately 12% of patients diagnosed with operable EC were aged 50 years or younger with advanced disease at presentation. Additionally, in a retrospective study, a significant proportion (20.8%) of patients presenting with operable EC was younger than 55 years old, and almost two-thirds of those presenting younger than 55 years had T3 stage tumors, which was significantly different than those older than 55 years (Hamouda et al, 2010). Likewise in the present results, the risk of developing EC was significantly decreased with aging in case-patients, which reinforces the surging incidence and prognostic outcome of EC in younger patients.…”
Section: Discussionmentioning
confidence: 98%
“…Previous studies have suggested that more aggressive treatment selection among young patients results in similar overall survival despite more advanced stage at diagnosis. 14,15,17,23 Although some studies demonstrate improved 5-year overall survival among younger patients, others fail to replicate these findings. [14][15][16][17][18][19]23 In this series, patients aged less than 75 years had a similar rate of receiving any surgical therapy, although patients aged less than 65 years were more likely to receive aggressive treatment with induction therapy þ surgery than older patients.…”
Section: Discussionmentioning
confidence: 99%
“…Most studies are single-institution experiences limited by small sample sizes and conflicting findings relating to the presentation, treatment, and prognosis of this population; as such, the clinicopathologic presentation and outcomes of esophageal cancer in young patients are not well defined. [14][15][16][17][18][19][20][21][22][23][24][25] Further complicating current understanding of this disease in young patients is the lack of consensus as to what constitutes a ''young patient,'' with many studies arbitrarily selecting age less than 50 years. [14][15][16][17][18][19][20][21] Given that survival for this disease remains poor, esophageal cancer in young patients merits further investigation to better guide diagnosis and management in this population.…”
Section: Perspectivementioning
confidence: 99%